Histomorphological study of the lymphoglandular complex in adult local breed dog (Canis familiaris) - Salah S. Obead; Luay O. Hamza (Iraqi Journal of Veterinary Sciences)
The morphological and histological features of the lymphoglandular complex of ten adult local breed dogs were studied. The dogs were hunted in cages and put in the animal house of Veterinary Medicine College / University of Baghdad. The dogs that were hunted and kept under supervision were then anesthetized, and slaughter was done to collect the samples of caecum. For the histological study, the abdominal region opened, and the cecum was identified and extirpated out properly, then washed with normal saline and immersed in adequate 10% neutral buffered formalin fixative for 72 hours at room temperature. After fixation, the specimens were washed with tap water and processed using routine histological techniques. Morphologically, the mucosa of the cecum had openings of the lymphoglandular complex that were randomly distributed and appeared as a rounded elevation at the upper caecum folds of the mucosal surface and in all portions of the caecum. Histologically, the lymphoglandular complexes in the tunica submucosa appeared rounded or oval in shape, which is closely related to the profound aspect of the muscularis mucosa, and they scarcely conquered the whole thickness of the submucosal layer. In the studied dogs, there were no cortical and medullary zones of the lymphoid structure of the lymphoglandular complex and didn’t have germinal centers. The conclusion of the current results represents that the lymphoglandular complex has a different structure from other lymphoid organs, which have a cortex and medulla in addition to germinal centers.